Designing a Waste Heat Recovery Heat Exchanger for Polymer Electrolyte Membrane Fuel Cell Operation in Medium-Altitude Unmanned Aerial Vehicles - Juwon Jang; Jaehyung Choi; Seung-Jun Choi; Seung-Gon Kim (Energies)
Polymer electrolyte membrane fuel cells (PEMFCs) are emerging as the next-generation powertrain for unmanned aerial vehicles (UAVs) due to their high energy density and long operating duration. PEMFCs are subject to icing and performance degradation problems at sub-zero temperatures, especially at high altitudes. Therefore, an effective preheating system is required to ensure stable PEMFC operation in high-altitude environments. This study aimed to mathematically model a shell-and-tube heat exchanger that utilizes waste heat recovery to prevent internal and external PEMFC damage in cold, high-altitude conditions. The waste heat from the PEMFC is estimated based on the thrust of the MQ-9 Reaper, and the proposed heat exchanger must be capable of heating air to −5 °C. As the heat exchanger utilizes only waste heat, the primary energy consumption arises from the coolant pumping process. Calculation results indicated that the proposed heat exchanger design improved the overall system efficiency by up to 15.7%, demonstrating its effectiveness in utilizing waste heat under aviation conditions.